Regional differences of the demographic ageing scale of Belarus and Russia - Antipova, Ekaterina A.; Trifonova, Zoya A. (Journal of the Belarusian State University. Geography and Geology, 2017)
The comparative geographical analysis of the demographic ageing in Belarus and Russia is given in the article. The article describes a system of indicators to assess the extent and the level of ageing and rationale for the use of ageing index is providing. With use of two international ageing scales made comparative conclusions about the prevailing stage of ageing are made. They are at a higher level of ageing in Belarus then in Russia at the macro geographical level and even-to the strong regional differentiation process in Belarus and Russia. In the work with ageing index the typology of Russian Federation by the subjects of federation for 1989 and 2002 and the typology of the administrative districts of Belarus for 1999 and 2015 by the level of demographic ageing are developed, indicating about the manifestation of inter-regional differentiation. Comparative analysis showed a higher degree of inter-regional differentiation of demographic ageing Russia than Belarus, which is based traced the dominant role of the ethnic factor. This is indicated by the coincidence of ethnic concentration regions in a particular type of ageing. Micro geographical level of analysis of Belarus shows the center-peripheral properties of demographic ageing and evidence about strengthening of differentiation between rural and urban areas. Interregional differentiation is expressed in a more favorable situation in the field of ageing in the Minsk region and Polesie and unfavorable – in the Vitebsk, Grodno and Mogilev regions.